2023
DOI: 10.3390/ijms24108514
|View full text |Cite
|
Sign up to set email alerts
|

Precise Regulation of the TAA1/TAR-YUCCA Auxin Biosynthesis Pathway in Plants

Abstract: The indole-3-pyruvic acid (IPA) pathway is the main auxin biosynthesis pathway in the plant kingdom. Local control of auxin biosynthesis through this pathway regulates plant growth and development and the responses to biotic and abiotic stresses. During the past decades, genetic, physiological, biochemical, and molecular studies have greatly advanced our understanding of tryptophan-dependent auxin biosynthesis. The IPA pathway includes two steps: Trp is converted to IPA by TRYPTOPHAN AMINOTRANSFERASE OF ARABID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 126 publications
0
8
0
Order By: Relevance
“…In addition, moderating auxin biosynthesis can regulate lateral organ initiation. The production of auxin primarily relies on tryptophan (TRP)-dependent biosynthetic pathways, where enzymes TAR and YUC are essential [ 42 ]. Studies on moss gametophores through tarac and yuccf mutants showed that inhibiting TAR and YUC genes can increase lateral branching and reduce apical dominance [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, moderating auxin biosynthesis can regulate lateral organ initiation. The production of auxin primarily relies on tryptophan (TRP)-dependent biosynthetic pathways, where enzymes TAR and YUC are essential [ 42 ]. Studies on moss gametophores through tarac and yuccf mutants showed that inhibiting TAR and YUC genes can increase lateral branching and reduce apical dominance [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the stress tolerance of 95-608 should be further compared with other varieties. Studies indicate that miRNA-directed regulation of transcription factors may also play key roles in the precise regulation of IPA-dependent auxin biosynthesis in plants ( Luo and Di, 2023 ). In this study, all MsYUCs contained at least three predicted targets for miRNA, suggesting a miRNA-directed regulation of YUC in M. sativa ( Figure 6C ).…”
Section: Discussionmentioning
confidence: 99%
“…In the frame of this pathway, first, Indole-3-pyruvic acid (IPA) was formed by the action of the TAA1 gene, and thereafter, numerous YUCCA genes were converted from IPA to IAA. Recently, the key role of the TAA1 gene and several auxin transporters in the process of the induction of embryos in plants was shown [ 120 , 121 ]. However, auxin itself, auxin “concentration” or level, cannot be used as a marker for any morphogenic processes.…”
Section: Major Aspects Of Plant Regenerationmentioning
confidence: 99%